Angular analysis of the B0 → K*0e+e- decay in the low-q2 region - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
An angular analysis of the B0 → K*0e+e− decay is performed using a data sample, corresponding to an integrated luminosity of 3.0 fb−1, collected by the LHCb experiment in pp collisions at centre-of-mass energies of 7 and 8 TeV during 2011 and 2012. For the first time several observables are measured in the dielectron mass squared (q2) interval between 0.002 and 1.120 GeV2/c4. The angular observables FL and ATRewhich are related to the K*0 polarisation and to the lepton forward-backward asymmetry, are measured to be FL = 0.16 ± 0.06 ± 0.03 and ATRe= 0.10 ± 0.18 ± 0.05, where the first uncertainty is statistical and the second systematic. The angular observables AT(2)and ATImwhich are sensitive to the photon polarisation in this q2 range, are found to be AT(2)= − 0.23 ± 0.23 ± 0.05 and ATIm= 0.14 ± 0.22 ± 0.05. The results are consistent with Standard Model predictions.